The gingerbread boy - Galdone, Paul. (New York : Clarion, 1975)
The Gingerbread Boy eludes the hungry grasp of everyone he meets until he happens upon a fox more clever than he.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
Book Links (A.L.A.), November 1998.
Library Journal, April 1995.
Booklist, May 1995.
Horn Book, April 2012.
Keywords: Folklore; Fairy tales; Gingerbread men -- Folklore